51 TO EXPLORE EMERGENCY MEDICINE SPRS UNDERSTANDING, IDENTIFICATION AND MANAGEMENT OF FRAILTY WITHIN THE EMERGENCY DEPARTMENT. (18th November 2021) - Loughlin, K M; McNamara, R; Timmons, S
Abstract: Background: Our frail cohort of older adults represent a large proportion of those presenting to our Emergency Departments. This has led to the introduction of diverse teams in many Emergency Departments to support their complex care needs. However, it is not known if Emergency Clinicians have a clear understanding of frailty identification and management or feel this is part of their own role. The aim of this study was to engage with Emergency Medicine Senior Trainees on the national training scheme in Ireland to explore their understanding of frailty and what they feel their role is in its identification and management. Methods: Following a literature review based on defined criteria, a number of focus groups were held with ED PGY4 and above doctors working in various Emergency Departments throughout the country, with thematic analysis of the transcripts of the focus groups. Results: In total, 13 Emergency Medicine PGY4 and above doctors partook in the focus groups with an overall view that frailty identification was part of their role within the Emergency Department; however there was agreement they have limited insight into the core principles of frailty identification and management. There was also an overall desire for future formal education on frailty to be provided. Three themes in the form of frailty recognition and assessment, education on frailty, and the role of the multidisciplinary team were identified as well as a number of subthemes for further exploration. Conclusion: The consequences of frailty often lead to presentation to the Emergency Department. There is an increased awareness of its presentation but the core providers of emergency care feel there is a lack of the education required for them to manage the consequences of frailty which they encounter on daily basis and they have a clear desire to increase the knowledge base and skill set.